Biometric characteristics of winter forage cereals grown under nitrogen fertilization in temperate rain conditions - Jamil, Muhammad; Ansar, Muhammad; Iqbal Ahmed, Zammurad; Ahmed, Tanveer; Shehzad, Muhammad; Ahmad, Aqeel; Mahmood, Imran (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The farmers of hilly areas face severe fodder shortage in winter season except to have only dry stalks of summer cereals. The study aimed to evaluate the adaptability of winter forage cereals (barley, oats, rye and triticale) and to quantify the suitable dose of nitrogen (0, 75, 150 and 225 kg.ha-1) for the assessment of bio-metric and qualitative characteristics of winter forage cereals (WFCs) at booting stage (BS) and milking dough stage (MDS) grown under temperate conditions. Two years (2016-2017 and 2017-2018) field trials were executed at the University of Poonch Rawalakot, Pakistan. Harvested forage then preserved as silage by adding Formic acid and Molasses as additives at the rate of 5 kg.t-1. Rye crop in conjunction with 225 kg.ha-1 nitrogen out yielded greater plant height which led to the highest green fodder (55413 and 43542 kg.ha-1) and dry matter yield (188471 and 12440 kg.ha-1) during consecutive years 2017 and 2018, respectively. Whereas, oats cultivar performed better for fresh weight, dry weight and leaf area per plant. More crude protein contents were recorded for triticale crop at N3 level with use of molasses during both the years at both cutting stages (booting and milking dough). More crude fibre was noted in barley crop at control level of nitrogen fertilization on both booting and milking dough stage. The correlation analysis revealed direct interrelationship among yield attributes and fodder yield of winter forage cereals and thus indicating the need to supply nitrogen at the rate of 225 kg.ha-1 for improving biometric characteristics of WFCs.